Mechanical Properties and Shrinkage of Ultrahigh-Performance Concrete Containing Lithium Carbonate and Nano-Calcium Carbonate - Tingyu Wang; Jianqing Gong; Bo Chen; Xiao Gong; Wanli Guo; Yang Zhang; Falei Li (Advances in Civil Engineering)
Early strength generation is essential for the successful application and usage of Ultrahigh-Performance Concrete (UHPC) in reinforcing concrete structures. The work contained in this paper focused on evaluating the effects of lithium carbonate (Li2CO3, denoted as LC) and nano-calcium carbonate (NC) on the early mechanical properties and autogenous shrinkage of UHPC under normal temperature curing conditions. In the study, scanning electron microscope (SEM) was utilized to investigate and quantify the morphology of the early hydration products. The corresponding results indicated that the 1-day comprehensive strength of the UHPC increased significantly with the addition of Li2CO3 and NC. Likewise, the addition of NC mitigated the loss of the 28-day compressive strength. For the materials evaluated, the 1-day compressive and flexural strengths reached peak values of 72.1 and 13.9 MPa, respectively, for optimum dosages of 0.075%∼0.1% Li2CO3 and 3%∼4% NC, respectively. The results also indicated that the combined LC-NC dosage had profound effects on the early autogenous shrinkage of UHPC, which could, however, be minimized by adjusting the Li2CO3 and NC dosages. That is, the combined dosage of the two early strength enhancers shortens the hydration induction period of cement whilst concurrently accelerating the hydration rate of the cement. The early strength agent increases the number of crystals in the hydration product and the crystal grain size becomes larger. These make the microstructure of the slurry more compact after hardening and therefore improve the overall performance of UHPC.